Walk through dark lands, Emilio Olsson and colportage as a travel experience - Escobar Sepúlveda, Darío (2022)
This article research the travel experience linked to the religious experience. To do this, he takes the case of the Protestant missionary, Emilio Olsson, who adopted colportage as a missionary strategy, which led to the installation of new Protestant projects in South America. We will reflect on the religious travel, seen from the discovery and evangelization, even in the nineteenth century. Our hypothesis holds that the introspective way of living and practicing their faith had an impact on the way of recognizing the Latin American territory at the same time that it had an impact on the way of exposing the strategic role of the increase in Protestant missionary practice in this same space.